The Influence of Financial Inclusion and Financial Technology on the Intention to Use Online Loans with Financial Behavior as a Mediating Variable - Kusumawati, Rahayu; Jagad, Daniel Jaya; Ginting, Medeilia Bernike Br (LITPAM, 2026)
This study aims to analyze the effect of financial inclusion and financial technology (fintech) on the intention to use online loans with financial behavior as a mediating variable. The background of this research is based on the phenomenon of the increasing use of online loan services in society, particularly in the Jakarta area, which on the one hand provides easier access to finance but on the other hand poses financial risks if not balanced with healthy financial behavior. This research employed a quantitative approach with a total of 96 respondents who were users of online loan services, determined using Cochran’s formula. Data were collected through questionnaires and analyzed using multiple linear regression and mediation testing with Hayes PROCESS Macro. The results show that financial inclusion has a positive and significant effect on both financial behavior and the intention to use online loans, while financial technology does not have a significant effect either on financial behavior or intention. Furthermore, financial behavior is proven to have a significant effect on the intention to use online loans. The mediation test indicates that financial behavior does not mediate the relationship between financial inclusion and the intention to use online loans but fully mediates the relationship between financial technology and the intention to use online loans. These findings emphasize that financial behavior is a dominant factor that needs to be strengthened in order for the use of online loans to provide optimal benefits. This study aims to analyze the effect of financial inclusion and financial technology (fintech) on the intention to use online loans with financial behavior as a mediating variable. The background of this research is based on the phenomenon of the increasing use of online loan services in society, particularly in the Jakarta area, which on the one hand provides easier access to finance but on the other hand poses financial risks if not balanced with healthy financial behavior. This research employed a quantitative approach with a total of 96 respondents who were users of online loan services, determined using Cochran’s formula. Data were collected through questionnaires and analyzed using multiple linear regression and mediation testing with Hayes PROCESS Macro. The results show that financial inclusion has a positive and significant effect on both financial behavior and the intention to use online loans, while financial technology does not have a significant effect either on financial behavior or intention. Furthermore, financial behavior is proven to have a significant effect on the intention to use online loans. The mediation test indicates that financial behavior does not mediate the relationship between financial inclusion and the intention to use online loans but fully mediates the relationship between financial technology and the intention to use online loans. These findings emphasize that financial behavior is a dominant factor that needs to be strengthened in order for the use of online loans to provide optimal benefits.